Comparison of Early Versus Delayed Laparoscopic Cholecystectomy in Acute Cholelithiasis (Medical Forum Monthly, 2020)
Objective: To compare the early versus delayed laparoscopic cholecystectomy in acute cholelithiasis.Study Design: Descriptive StudyPlace and Duration of Study: This study was conducted at the DHQ Teaching Hospital Gujranwala during May 2019 till October 2019.Materials and Methods: This study was conducted with the permission of ethical committee of hospitals. There were 50 patients that were included in this study. All patients were subjected to laparoscopic cholecystectomy.Results: The data was collected from 50 patients. The data was divided into two groups, one was early group and one was delayed group. Both groups contain 25 patients. The data of these two groups were compared in terms of age, pathological parameters and ultrasound findings.Conclusion: It is concluded that both methods of laparoscopic cholecystectomies are reasonable and safe in acute cholecystitis patients.